NILAI-NILAI SOSIAL DALAM NOVEL MEMBURU KASIH PEREMPUAN SAMPAN KARYA ABDUL KADIR IBRAHIM - Suriyanto '; Nursal Hakim; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research titled Social Values In Novel Memburu Kasih Perempuan Sampan written by Abdul Kadir Ibrahim. This study aims to describe the social values in the novel Memburu Kasih Perempuan Sampan written by abdul kadir ibrahim. The method used in this research is qualitative research method descriptive analysis. The data of this research are social values in the novel Memburu Kasih Perempuan Sampan written by abdul kadir ibrahim published by the roots of Indonesia which contains 46 chapter stories with many backgrounds in the Riau Islands region. The results of the study found 73 with 8 social values that is, social values of society, union, affection, deliberation, economy, recreation, mutual help, and character. The data include social values of the community as much as 4, the social value of the union as much as 21, the social value of love as much as 12, the social value of musyawarah as much as 10, the socioeconomic value of 5, the social value of recreation as much as 3, the social value of the mutual help as much as 9, and The social value of the character as much as 9. Social values are much influenced by the social value of the union and the social value of affection with being covered by other social values.Keywords: Social Value, Novel